2024
DOI: 10.1002/jmv.29336
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gut–lung axis crosstalk in SARS‐CoV‐2 infection: Insights from a hACE2 mouse model

Yu Zhang,
Yifang Ma,
Weiyang Sun
et al.

Abstract: Based on the forefront of clinical research, there is a growing recognition that the gut microbiota, which plays a pivotal role in shaping both the innate and adaptive immune systems, may significantly contribute to the pathogenesis of coronavirus disease 2019 (COVID‐19). Although an association between altered gut microbiota and COVID‐19 pathogenesis has been established, the causative mechanisms remain incompletely understood. Additionally, the validation of the precise functional alterations within the gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…In recent years, there is a growing evidence show that the gut microbiota, which plays a pivotal role in shaping both the innate and adaptive immune systems, may significantly contribute to the pathogenesis of COVID‐19 ( 62 ). The clinical researches found that a notable aspect of COVID‐19 is the prevalence of severe gastrointestinal symptoms reported by approximately 50.5% of affected individuals ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there is a growing evidence show that the gut microbiota, which plays a pivotal role in shaping both the innate and adaptive immune systems, may significantly contribute to the pathogenesis of COVID‐19 ( 62 ). The clinical researches found that a notable aspect of COVID‐19 is the prevalence of severe gastrointestinal symptoms reported by approximately 50.5% of affected individuals ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…A clear collection between SARS-CoV-2 infection and notable abnormalities in the gut microbiota, which marked as a decreased bacterial diversity, an increased opportunistic pathogens, a depletion of beneficial commensal organisms, and impaired biosynthesis of essential metabolites was established ( 65 70 ). In the humanized ACE2 knock‐in (hACE2‐KI) mouse model, a notable reduction in intra‐individual bacterial richness (α‐diversity) and distinct variations in intergroup microbiota composition (β‐diversity), was observed following SARS-CoV-2 infection ( 62 ). In our study, we found that α-diversity and β‐diversity were recovered with the AGE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Age, comorbidities, and a lack of viral control contribute to poor clinical outcomes [12] . SARS-CoV-2 infection, particularly in elderly and weakened immunes, may involve auxiliary proteins and the human microbiota, but its impact is controversial, necessitating further investigation [48] . Due to the virus SARS-CoV-2, the RNA one that is causing COVID-19, terribly disrupted the virome of human gut, the intestinal microbiome that is highly abundant in the human body compared to the rest.…”
Section: Introductionmentioning
confidence: 99%